Advances Towards Ex Situ Conservation of Critically Endangered Rhodomyrtus psidioides (Myrtaceae) - Hardstaff, Lyndle; Funnekotter, Bryn; Sommerville, K.D.; Offord, C.A.; Mancera, Ricardo (2025)
Rhodomyrtus psidioides (G.Don) Benth. (Myrtaceae) is a critically endangered rainforest species from the east coast of Australia, where populations have severely and rapidly declined due to the effects of repeated myrtle rust infection. With very limited material available in the wild and freezing-sensitive seeds that have prevented storage in a seed bank, ex situ conservation of this exceptional species has proven difficult. Material from a seed orchard grown at the Australian Botanic Garden Mount Annan was successfully used to initiate three new accessions into tissue culture from cuttings, and to undertake cryopreservation experiments using a droplet-vitrification (DV) protocol for both seeds and cultured shoot tips. Use of seedling material for tissue culture initiation was very effective, with a 94–100% success rate for semi-hardwood explants and a 50–62% success rate for softwood explants. Although no survival of seeds after cryopreservation was observed, seeds of R. psidioides showed some tolerance of desiccation and exposure to cryoprotective agents. Regeneration after cryopreservation using a DV protocol was demonstrated in only one shoot tip precultured on basal medium containing 0.4 M sucrose and incubated in PVS2 for 20 min prior to immersion in liquid nitrogen. These results demonstrate the value of living collections in botanic gardens for conservation research, highlight the importance of germplasm choice for tissue culture initiation, and demonstrate the potential of cryobiotechnologies for the ex situ conservation of exceptional plant species.